Perceptions, practices, and associated factors towards expressed breastfeeding among mothers in Jakarta, Indonesia - Pambudi, Wiyarni; Dewanto, Naomi Esthernita Fauzia; Yusra, Yusra; Werdhani, Retno Asti; Endaryanto, Anang; Fahmida, Umi; Alatas, Fatima Safira; Hegar, Badriul (Indonesian Pediatric Society, 2024)
Background Expression of breast milk is a strategy to ensures continuous breastfeeding during temporary separation of infant from the mother. Handling and storage of expressed breast milk (EBM) should be based on established recommendations because these practices can affect milk quality and safety. Objective To describe perceptions and practices of EBM handling and storage, compare with commonly used recommendations and associated factors influencing these practices among mothers in Jakarta, Indonesia, Methods Mothers who practiced expressed breastfeeding (EBF) to their 6-12 weeks-old infants completed questionnaires about their peceptions and practices on how they handle and storage EBM. The differences in perceptions and practices about expressed breastfeeding management were analyzed using the Chi-square or Fisher's exact test. Results Among 30 mothers, 14/30 gave EBF exclusively, 19/30 used breast pump, and 26/30 expressed ³6 times/day. Infants in this study received expressed milk 5-10 times per day. Maternal age and resource of information were factors significantly associated with mother’s perceptions, while maternal age, education, and parity were significantly associated with the practices of EBM handling and storage. Conclusion This study reveals inconsistent perceptions and practices on expressed milk handling and storage by the mothers. They have good knowledge about the theoretical aspects of expressed breastfeeding, but some other techniques are poor, which can be detrimental to the health of the infants. Further study is needed to find more efficient and optimal methods of expressed milk handling and storage, necessitating thoughtful consideration of better practices and recommendations.